Description and seasonal detection of two potential whale calls recorded in the Indian Ocean - Sousa, Andreia G; Harris, Danielle (The Journal of the Acoustical Society of America, 2016)
Unidentified acoustic signals are recorded by hydrophones placed in the world's oceans. Some of these sounds are suspected to originate from marine mammals. In this study, two acoustic signals recorded by two arrays at Diego Garcia in the northern Indian Ocean are described. Data were available between January 2002 and December 2003. Signals were detected manually using long-term spectral average plots. Time and frequency measurements were taken from a sample of both signals. The first unidentified signal [Diego Garcia Downsweep (DGD)] consisted of two main components. The mean frequency range of the entire signal was 19.3-45.0 Hz, with a mean duration of 36.5 s (n = 22). Detections of DGD at the northern array peaked in the austral summer, though detections at the southern array peaked during winter and spring. The second unidentified signal [Diego Garcia Croak (DGC)] consisted of one component with a mean frequency range of 16.9-49.6 Hz. The mean duration of the signal was 13.1 s (n = 10). Detections of DGC did not follow a clear seasonal pattern. These signals followed characteristics of biological sources, suggesting that they could be whale calls. Fin whale calls and possible blue whales D-calls were also identified in the data. Peer reviewed